Ovarian Carcinosarcoma and Concurrent Serous Tubal Intraepithelial Carcinoma With Next-Generation Sequencing Suggesting an Origin From the Fallopian Tube. (August 2019) - See, Sharlene Helene C.; Behdad, Amir; Maniar, Kruti P.; Blanco, Luis Z.
Background . Ovarian carcinosarcomas are rare aggressive biphasic tumors. Evidence suggests that these tumors are monoclonal and that the sarcoma component is derived from a stem cell undergoing divergent differentiation. Currently, there remains a paucity of data regarding its origin, with few reports suggesting an association with serous tubal intraepithelial carcinoma (STIC) by immunohistochemistry and genetics. Objective . We sought to determine the relationship of carcinosarcoma to high-grade serous carcinoma and STIC by investigating for similar mutation signatures through next-generation sequencing. Methodology. A case of carcinosarcoma with associated high-grade serous carcinoma and STIC was macrodissected, and next-generation sequencing was performed on each component separately. Results. The STIC, high-grade serous carcinoma component, and chondrosarcoma component were all diffusely positive for p53 and p16 by immunohistochemistry. Next-generation sequencing demonstrated an identical TP53 gene c.376-1G>A 5' splice site pathogenic mutation in all 3 components. Conclusions . Our findings suggest that carcinosarcomas may also originate from the fallopian tube.